YOUNG GENERATION IN THE PRESERVATION OF THE TABOT TRADITION OF BENGKULU CITY FROM THE PERSPECTIVE OF SOCIAL IDENTITY THEORY: Generasi Muda Dalam Pelestarian Tradisi Tabot Kota Bengkulu Dalam Perspektif Teori Identitas Sosial - Robinson, Andika; Jefri Setyawan (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This research raises the urgency of preserving the Tabot tradition in Bengkulu City, which plays an important role in shaping social identity and social harmony amid the challenges of globalization. This research aims to understand how the younger generation plays a role in preserving the Tabot tradition as a cultural symbol and collective identity and how this tradition strengthens social ties in a multicultural society. This research used a qualitative approach with a case study design, where data was obtained through semi-structured interviews with participants actively involved in the Tabot tradition. The sampling technique used was purposive sampling, and data analysis was conducted using thematic analysis techniques. This study found that the participation of the younger generation in the Tabot tradition not only strengthens the sense of local cultural pride and identity but also enhances social cohesion in a diverse society. The main implication of this study is the importance of understanding the role of cultural traditions in shaping social identity and building social capital, which can be a foundation for strengthening the sustainability of local culture in a modern context.